THE EFFECT OF PARTICIPATORY LEADERSHIP, COMMUNICATION SKILLS, SOCIAL SKILLS, AND TRUST ON SOCIAL RESPONSIBILITY (CAUSAL STUDY IN BOGOR REGENCY, WEST JAVA PROVINCE) - Author (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study is to find the effect of the effect of participatory leadership, communication skills, social skills, and trust on social responsibility. This study was using survey method where the data had been analyzed by path analisis after the variable data had been input to correlation matrix. In this study, the respondents were the head of family that had been chosen as analysis unit and 115 samples were chosen randomly. The result of the study found the People about Social responsbility at Bogor was influenced directly by participatory leadership. Besides that, it was found the People social responsibility was found that People social responsibility was influenced indirectly by communication skills, social skills, and trust. Based on the finding, it can be concluded that variation that has happened to People social responsibility in Bogor Regency probably has been influenced by variation of participatory leadership, communication skills, social skills, and trust